Pengaruh Penggunaan Gadged Terhadap Perilaku Sosial Anak Usia Dini di Dusun Seran, Desa Rumbuk Timur, Kecamatan Sakra Tahun 2023 - Vera Santina Br. Sembiring; Restu Monika Nia Betaubun; Suratni Suratni (PAPSEL Research and Consulting, 2024)
This study aims to determine the effect of Gadget use on the social behaviour of early childhood in Seran Hamlet, East Rumbuk Village, Sakra District in 2023. Research data were collected through questionnaires given to parents or guardians of early childhood living in Seran Hamlet. The research method used is a quantitative approach with direct data collection. The research sample consisted of 28 early childhood. Data collection techniques include observation, questionnaires, and documentation. Data analysis was conducted using the simple regression method to evaluate the relationship between the independent variable, namely Gadget Use, and the dependent variable, namely Early Childhood Behaviour. The results showed that there is a correlation and influence between the use of Gadgets and early childhood behaviour, with a correlation coefficient that exceeds the alpha (5%) significance level, namely 0.45> 0.05. Based on the analysis conducted, the results showed that the use of Gadgets has a negative relationship with early childhood behaviour, with a significance level of -91.289. Therefore, it can be concluded that the use of Gadgets has a negative impact on early childhood behaviour in Seran Hamlet. Keywords: Early childhood, Gadged use, Social behaviour